THE EDUCATION OF CHARACTER OF THE VOCATIONAL HIGH SCHOOL OF PLERET BANTUL YOGYAKARTA INDONESIA - Sutarman, Sutarman; Parjiman, Parjiman; Chirzin, Muhammad (EARR (Educational Administration Research and Review), 2023)
This research aims to find out the deeper on the character education in SMKN (vocational school) Pleret Bantul Jogjakarta which covers: (1) some patterns of religious values education in Vocational High School of Pleret Bantul Yogyakarta students, namely: (a) do praying before and after the activities (studying); (b) To do Dhuhur and Asar prayers in the mosque ;  (c) Dhuha prayer; (d) To read Al-Qur`an every morning in Ramadhan before learning teaching process; (e) Sunnah fasting of Monday-Thursday, f. hadroh music; (2)  the internalization of emotional quotient; and (3) It is the positive effect of character education toward students of SMKN Pleret Bantul. The research was  a  descriptive qualitative approach. Technique of data collection by interview, observation of participant and documentation. The data analysis was by reduction, display and provided conclusions. The result of this study shows : (1) the transformation of Spiritual Quotient values : Various patterns of character values education are beneficial to the values of the students' faith of the character values. Students had religiosity is a way of religious individuals who incorporate religious values into their personalities; (2) the emotional quotient values which is described in the character values of students, namely: students have empathy attitude to help another, have good self-awareness, have moods and emotions, and have the high motivation  and have ability to build good communication with another; (3)there are the positive effect of Spiritual Quotient (SQ) values and emotional quotient (EQ) in students’ character and have good academic achievement.